Smartize and Humanize People in the Village for Every Pandemic - ., Sukarso; Paramarti Dasuki, Niken; Noviko, Sendy (KnE Social Sciences, 2023)
The use of the internet in the village has risen to the smart-village concept in which the communication pattern between members of the village community uses the internet effectively and efficiently. The use of internet-based social media is also increasing in both frequency and intensity. However, the traditional pattern of village communities, which are more personal and flexible, creates a gap with applying smart villages that are impersonal, mechanical, and precise. Therefore, it is interesting to examine the application of smart villages that are to the conditions of the village community; in this case, the application of smart villages that are more realistic to the needs of the community, namely humanized smart villages or humanized-smart villages. This study uses a case study approach by comparing two villages that represent villages close to urban areas and those relatively far from urban areas. The results of this study show that the use and utilization of the internet will naturally create marginal or non-eligible community groups. Therefore, in the concept of a humanized smart village, a model can be formulated that allows these marginalized communities to be intensely involved in using the internet and social media. The model is characterized by inclusive, deconstructive, mediation, and institutionalization. In this concept, humanized or humane is indicated by fulfilling the rights of community groups who can’t use and utilize the internet and social media to become systematically involved. Keywords: humanized smart villages, inclusive, deconstructive, mediation, institutionalization